Survey On The Level Of Physical Fitness Of Students Aged 10-11 After The Covid-19 Pandemic At state elementary school Kaliboto 3, Tarokan District, Kediri Regency In 2022/2023 - Juang Febri Imanda; Budiman Agung Pratama; Reo Prasetiyo Herpandika (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2023)
During the post-pandemic physical fitness, many changes have occurred in education. Changes in learning methods to the technological tools used have an impact on reducing the activity of today's children in moving. The formulation of the problem posed is what is the condition of the physical fitness level of students aged 10-11 after the Covid-19 pandemic at SD N Kaliboto 3, Tarokan, Kediri Regency in 2022/2023? This research uses descriptive quantitative research using percentage descriptive method. One of the variables in this study was the Nusantara Student Fitness Test (TKPN) with the sample of this study using 63 Kaliboto 3 Public Elementary Schools, Tarokan District, Kediri Regency. The results of the study found that BMI in the category of good nutrition was 63%, but not supported by physical fitness which had an adequate category with a proportion value of 2.9. So that the TKPN results for students aged 10-11 SD Negeri Kaliboto 3, Tarokan District, Kediri Regency have a moderate category.